The value of electron microscopy in the diagnosis of renal disease (Journal of Medical Science, 2016)
In the literature of recent years there are few publications on the importance of research in electron-microscopic pathomorphological diagnosis of kidney disease. The most important, which is diagnosed only on the basis of these studies are: minimal change disease, assessment of mesangial cell proliferation as well as the differentiation of the types of membranoproliferative glomerulonephritis, fibrillary glomerulonephritis, lupus nephritis, thin basement membrane disease, Alport syndrome, hemolytic-uremic syndrome. This report presents the most characteristic features of the ultrastructure allowing for diagnosis of these diseases.